Nonfatal, Nonpredatory Jaguar Attacks in Brazil: A Case Series - Haddad, Vidal [UNESP]; Francisco de Campos Neto, Manoel; Barreiros, João Pedro (SAGE Publications, 2022)
The jaguar, Panthera onca (Linnaeus, 1758), is the biggest felid in the Americas. Its range extends from the southwestern United States to northern Argentina. Herein, we present 5 nonfatal jaguar attacks that occurred in Brazil between March 2010 and November 2021. Most of the cases occurred when the victim encountered a jaguar guarding its food or cubs or devouring prey; none appeared to be the result of predatory behavior.
Keywords: animal attacks on humans; animal bite and scratch injuries; large felid attacks on humans